2019
DOI: 10.1037/neu0000471
|View full text |Cite
|
Sign up to set email alerts
|

Strategy bias in the emotion regulation of high trait anxiety individuals: An investigation of underlying neural signatures using ERPs.

Abstract: Objective: Previous studies have employed self-report measures to investigate emotion regulation (ER) strategy biases in individuals with anxiety. We investigated the neural signatures underlying ER strategy biases. Method: Twenty individuals with high trait anxiety (HTA) and twenty individuals with low trait anxiety (LTA) completed both the Emotion Regulation Questionnaire and ER tasks. During the tasks, participants were required to passively view, reappraise, and suppress expression while viewing negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Specifically, we found that individuals who conducted WMT showed significant reductions in LPP during the process of cognitive reappraisal. Even if the lack of reflection on subjective ratings, the modulated neurological indicator (which might exclude the demand characteristics and be more sensitive, Pan et al, 2019) implied the improvements in reappraisal ability among WMT trainees. Indeed, the increased self-reported positive refocusing in two WMT groups also provided consistent evidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we found that individuals who conducted WMT showed significant reductions in LPP during the process of cognitive reappraisal. Even if the lack of reflection on subjective ratings, the modulated neurological indicator (which might exclude the demand characteristics and be more sensitive, Pan et al, 2019) implied the improvements in reappraisal ability among WMT trainees. Indeed, the increased self-reported positive refocusing in two WMT groups also provided consistent evidence.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined distraction as another explicit emotion regulation manner but found no difference for its LPP reduction between the training groups and the control group. In fact, compared with reappraisal, distraction was considered to involve less cognitively demanding and top-down control (Schönfelder, Kanske, Heissler, & Wessa, 2014) and was also found to be less impaired in anxious individuals (Pan et al, 2019). Therefore, it is difficult to be influenced by cognitive training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This part of the results reveals the unique emotions of anxious individuals and the brain networks related to working memory. In short, these results suggest an important cognitive basis for anxiety disorders and provide unique evidence for the neural mechanism of the interaction between anxiety and working memory [ 147 , 148 ].…”
Section: Conclusion and Prospectmentioning
confidence: 99%